So I have applied the FOIL method to multiply my intial question which is:

If A = 1 + j2 and B = 2 - j3

(a+bj) (c+dj) = ac +adj + bcj +bdi^2

so,

(1 +j2)+(c+dj) = (1 x 2) + (1 x 3) + (2 x 2) + (2 x 3)

= 2 + 4j + 4j +6j^2 = This is where my problem comes.......

=3 + 4j +4j + -6 ? I am assuming the - is to satisfy B equation?

Going through this method I reach an answer with single digits....5

I would assume A second number to show real and imaginary parts. Is this correct or am I missing something?

If A = 1 + j2 and B = 2 - j3

(a+bj) (c+dj) = ac +adj + bcj +bdi^2

so,

(1 +j2)+(c+dj) = (1 x 2) + (1 x 3) + (2 x 2) + (2 x 3)

= 2 + 4j + 4j +6j^2 = This is where my problem comes.......

=3 + 4j +4j + -6 ? I am assuming the - is to satisfy B equation?

Going through this method I reach an answer with single digits....5

I would assume A second number to show real and imaginary parts. Is this correct or am I missing something?

Last edited: